Relationship between fiscal policy and balance of payment on economic growth in Nigeria (Lapai Journal of Economics, 2018)
This study investigates the relationship between fiscal policy and balance of payments on economic growth in Nigeria from 1984 to 2017. The method employed is Autoregressive Distributed Lag (ARDL) using variables such as government expenditure, balance of payments, unemployment, real exchange rate, inflation and economic growth. The study revealed that Nigeria absorb more than what the economy produce (that is, domestic expenditure and investment are greater than National income) which result to balance of payment (BOP) deficit arising from over population as compared to productive sector of the economy. The result also shows a positive and significant relationship between unemployment and economic growth. Government expenditure is negatively related to economic growth in short-run, however, in the long run it is positive through infrastructures; inflation is positive in short run while it is negative in the long run; Exchange rate reveal negative and significant relationship with economic growth. It is concluded that balance of payments deficit and over population it’s a curse to the economy, it is recommended that Absorption and Devaluation of currency to improve export and deteriorate import through policy induced approach.